Aṡar Istikhdām al-Qiṣṣah al-Muṣawwarah Bi aṭ-Ṭarīqah al-Mubāsyirah Fī Tanmiyah at-Ta`bīr asy-Syafawī Laday Ṭalabah aṣ-Ṣaff al-Awwal aṡ-Ṡānawi (Dirāsah Tajrībiyyah Bi Madrasah Insān Quranī, Aneuk Batee) - Ziyaush Shabri; Nur Chalis (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
The Students of Modern Islamic Boarding Schools are distinguished in learning a variety of languages, one of which is Arabic. The teacher's method in Arabic learning is by using the audiolingual method. This method mostly involves memorizing vocabulary and Arabic grammar. However, the educators mostly use dialogue methods in teaching, of course; this process will be a good attempt to improve the ability of students to chat in Arabic. But in fact, many students are weak and unable to match the vocabulary and Arabic grammar that have memorized in the conversation. Therefore, the researcher examined the topic "Implications of Using Direct Picture Stories in the Development of Expressing Verbal Expression" to facilitate students in applying what they have learned from Arabic vocabulary and grammar in order to improve their ability to express these expressions. The purpose of this research is to identify the effectiveness of the direct method with the illustrated stories media in improving the ability of oral expression and its application in Arabic subjects for first graders Madrasah Aliyah Insan Qur'ani. The research method is experimental, therefore the researcher collects data based on test result data from the application of the method using empirically illustrated stories. The object group in this study is all the first graders of Madrasah Aliyah Insan Qur'ani Aneuk Batee which numbered 174 students. The researcher selected several samples and made them two classes of students, namely class D as a control group of 20 students and class E as an experimental group with 20 students. The result of this study is that the application of a direct method with illustrated stories in the learning of expressing expressions orally is effective in improving students' ability in conversation. Because the T-Test score in the calculation is 2.93 greater than the T-Test table value of 1,685. So the difference between the experimental group and the control group is clear and unquestionable.